Synthesis, characterization and thermal studies of solid state 4-methylbenzylidenepyruvate of some trivalent metal ions - Mendes,R.A. (2005)
Solid state compounds of 4-methylbenzylidenepyruvate with Al(III), Ga(III), In(III) and Sc(III) have been synthesized. Complexometry, X-ray powder diffractometry, infrared spectroscopy and simultaneous thermogravimetry-differential thermal analysis (TG-DTA) have been used to characterize and to study the thermal behavior of these compounds. The results provided information concerning the stoichiometry, crystallinity, thermal stability and thermal decomposition of these compounds.